PENENTUAN KADAR FENOLIK TOTAL EKSTRAK ETANOL DAUN NILAM (Pogostemon cablin Benth.) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Masdiana Tahir; A. Muflihunna; Syafrianti Syafrianti (Jurnal Fitofarmaka Indonesia, 2017)
One of the plants that is well known in the community and is used as a traditional medicine is patchouli (Pogostemon cablin Benth.). It contains essential oils, flavonoids, saponins, tannins, glycosides, terpenoids and steroids. The alcohol content, such as patchouli alcohol and its derivatives, phenol, and a group of terpenoids in patchouli oil has antibacterial activity. The aim at this research to determine the total phenolic condition the ethanol extract from the patchouli leaves. The extract obtained was analyzed ist content using UV-Vis spectrophotometer. The measurements were done at the maximum wavelength of 662,85 nm. The result showed that the total phenolic in patchouli leave is 327,84 mgGAE /gram of extract.